2012
DOI: 10.1016/j.ab.2012.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence polarization assay for inhibitors of the kinase domain of receptor interacting protein 1

Abstract: Necrotic cell death is prevalent in many different pathologic disease states and in traumatic injury. Necroptosis is a form of necrosis that stems from specific signaling pathways with the key regulator being RIP1, a serine/threonine kinase. Specific inhibitors of RIP1, termed necrostatins, are potent inhibitors of necroptosis. Necrostatins are structurally distinct from one another yet still possess the ability to inhibit RIP1 kinase activity. To further understand the differences in the binding of the variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…However, based on the previous reports for similar compounds, some discrepancies were identified between the reported and expected data. Three of the five studies involved elemental analysis 15 , TLC analysis 18 , or no analytical data 20 . Besides the aforementioned five studies, five other studies reported nucleophilic substitution of 6 , although the preparation procedure for 6 was not described 22 26 .…”
Section: Introductionmentioning
confidence: 99%
“…However, based on the previous reports for similar compounds, some discrepancies were identified between the reported and expected data. Three of the five studies involved elemental analysis 15 , TLC analysis 18 , or no analytical data 20 . Besides the aforementioned five studies, five other studies reported nucleophilic substitution of 6 , although the preparation procedure for 6 was not described 22 26 .…”
Section: Introductionmentioning
confidence: 99%
“…13). 100 In this assay, the tested DMSO was tolerated up to 5%, and Z′ scores for 49 and 50 were 0.62 and 0.57, respectively. Takeda Pharmaceutical developed the BODIPY probe 51 based on compound 32 for TR-FRET, which was useful to not only measure the binding affinity for RIPK1 but also determine the kinetic profiles of the target compounds.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 80%
“…GSK developed a fluorescently labeled ATP-competitive ligand for the FP assay to compete with a small molecule. ,, Degterev et al synthesized two fluorescein-labeled probes based on Nec-1 (compound 49 ) and Nec-3 (compound 50 ) for an HTS FP assay (Figure ). In this assay, the tested DMSO was tolerated up to 5%, and Z ′ scores for 49 and 50 were 0.62 and 0.57, respectively. Takeda Pharmaceutical developed the BODIPY probe 51 based on compound 32 for TR-FRET, which was useful to not only measure the binding affinity for RIPK1 but also determine the kinetic profiles of the target compounds …”
Section: Discovery Of Necroptosis Inhibitorsmentioning
confidence: 90%
“…This protein displayed kinase activity in a 32 P autophosphorylation assay but lacked inhibition with the optimized RIP1 inhibitor Necrostatin-1 (Opt Nec-1, Figure 1B, C). Opt Nec-1 inhibits the activity of the baculovirus expressed GST-RIP1 fusion protein proteins [14] [19] suggesting that the His tagged version of RIP1 may not be folded correctly. RIP1 is a known client protein of Hsp90 in mammalian cells [20], therefore, we tested a co-infection of the Hsp90 co-chaperone Cdc37 and RIP1-His baculoviruses together in Sf9 cells.…”
Section: Resultsmentioning
confidence: 99%
“…To check if purified RIP1-His behaves the same as GST-RIP1 [19] and mammalian expressed RIP1 [14], we performed a radiometric kinase assay with different necrostatins as well as the corresponding inactive analogs (Figure 1A, 3E). The necrostatins are in three different structural classes: hydantoin-containing indole derivative (Nec-1), tricyclic derivative (Nec-3), and pyrrole derivative (Nec-4).…”
Section: Resultsmentioning
confidence: 99%